GERAKAN EKONOMI PESANTREN (Studi atas Pesantren Sidogiri Pasuruan) - Moh. Nadir (Universitas Wahid Hasyim Semarang, 2017)
Pesantren is generally a traditional educational institution that still retains the values salafiyahnya , however, boarding is always dynamic, because boarding schools in the total picture, revealing himself as a parameter, a factor that characterizes the lives thicker wider community , both in rural and urban areas in our country Indonesia. Because boarding an integral part of society , have a responsibility to develop and empower people in all fields, whether social, cultural, and economic. Pesantren Sidogiri which is an integral part of the community, enough interest to provide solutions problems that exist in the middle masyaraka, such as economics . (Boarding School in general is an educational institution that still maintain traditional values salafiyahnya , however , boarding is always dynamic , Because boarding schools in the total picture , revealing himself as a parameter , a factor that characterizes the lives thicker wider community groups, both in rural our country and urban Indonesia . boarding Because an integral part of society , have a responsibility to develop and empower people in all fields , Whether social, cultural, and economic. Pesantren Sidogiri the which is an integral part of the community, enough interest to provide solutions problems that exist in the middle masyaraka, such as economics).